Phomopsis head rot caused by Diaporthe helianthi : A new disease on sunflower in Argentina - Colombo, Denis Nahuel; Figueruelo, Andrea Mariana; Paniego, Norma Beatriz; Comerio, Ricardo Mario; Corro Molas, Andres Ezequiel (Wiley, 2024)
During a survey conducted in the 2021, 2022 and 2023 seasons, sunflower heads showing symptoms of dry rot were collected from 80 fields in the semi-arid Pampa region of Argentina. A total of 72% of the fields examined in 2021, 71% in 2022 and 63% in 2023 showed the presence of the disease. The highest incidence was recorded as 70% in 2021. Phomopsis head rot began as dry, brown spots on the back of the head, progressing to necrosis and twisting of adjacent leaves. Infected head tissue samples were surface sterilised, cultured on potato dextrose agar (PDA) and incubated at 25°C for 14 days. Diaporthe helianthi was identified based on cultural and morphological characteristics as well as molecular data. A phylogenetic analysis was performed. Internal transcribed spacer (ITS), translation elongation factor 1-α (ef1-α) and β-tubulin sequences were deposited in GenBank, showing the identity with the ex-type D. helianthi strain CBS 592.81. Pathogenicity experiments confirmed the presence of similar disease symptoms in inoculated sunflower heads, and D. helianthi was consistently reisolated from these organs. Our Koch's postulates testing results on heads constitute the first confirmed report that D. helianthi is the cause of Phomopsis head rot on sunflower in Argentina.